Determination of plasma melatonin levels by enzyme-linked inmunoabsobent assay (EIA) in turbot (Scophthalmus maximus L.) and tench (Tinca tinca L.) - Rebollar, P.J.; Ubilla, E.; Peleteiro-Alonso, J.B. (José Benito); Alvariño, M. (Centro Oceanográfico de Vigo, 2014)
An enzymoimmunoassay (EIA) kit for plasma melatonin (MLT) measurements was employed in tench (Tinca tinca) and in turbot (Scophtalmus maximus). Tench and turbot plasma samples were purified with a C18 reversed phase extraction columns because this kit is designed for human serum measurements. The lowest detection limit of the technique was 11.48 pg/well with a sensitivity at 50% binding of 100 pg/well. Intra-assay and inter-assay CV (%) were always less than 5% (n=8), and 9% (n=6) in tench plasma samples, and less than 5% (n=8) and 13% (n=5) in turbot plasma samples, respectively. Correlation coefficients between EIA and RIA measurements in tench and turbot plasma samples were 0.93 and 0.89 (p<0.001) respectively. Diurnal and nocturnal plasma melatonin mean levels were 14.7+/-2.1 pg/ml and 87.4+/-11 pg/ml in tench (n=15), and 3.5+/-0.4 pg/ml and 28.1+/-2.1 pg/ml in turbot (n=15). These species showed a melatonin circadian rhythm as in other animals studied. The results suggest that the commercial kit used in this experiment could be a suitable and alternative method to RIA for plasma MLT determinations in tench and turbot although it is necessary to increase volumes (1ml) and concentrate daytime samples. 1